Is female sex an independent risk factor for early mortality in isolated coronary artery bypass graft? A propensity-matched analysis. Issue 9 (September 2018) - Garatti, Andrea; Parolari, Alessandro; Canziani, Alberto; Mossuto, Eugenio; Daprati, Andrea; Abu Farah, Ali; Brugnetti, Daniele; Ranucci, Marco; Menicanti, Lorenzo
Abstract : Aims: Despite several studies reporting a higher mortality rate for women undergoing isolated coronary artery bypass graft (CABG) surgery, this issue has not been completely clarified. The aim of the current study was to determine if sex differences in CABG surgery affect adjusted operative results and operative mortality. Methods: Between January 2005 and December 2012, 3756 consecutive patients (3009 men and 747 women) underwent isolated CABG at our institution. Women presented with older age, smaller BSA and higher rate of preoperative comorbidities. The propensity score methodology was used to obtain risk-adjusted outcome comparisons between the two groups. Results: The distribution of preoperative variables among matched pairs (553 patients in both groups) was, on average, equal. Propensity-matched women received a similar number of distal anastomoses ( P  = 0.56), had similar rate of left internal thoracic artery (LITA) graft ( P  = 0.73) and comparable extracorporeal circulation ( P  = 0.61) and aortic cross-clamp ( P  = 0.39) time as men. Postoperative complications were comparable in the two study groups with the exception of postoperative transfusion rate which was significantly higher in women ( P  = 0.01). However, operative mortality (3.8 vs. 2.7%; P  = 0.20), perioperative acute myocardial infarction ( P  = 0.50) and stroke ( P  = 0.75) were not significantly different between the two groups. Interestingly, after adjustment for the other baseline characteristics, female patients with diabetes ( P  = 0.03), preoperative renal dysfunction ( P  = 0.07) and obesity ( P  = 0.07) exhibited a greater operative mortality rate compared with men with the same comorbidities. Conclusion: After adjustment for preoperative variables, female sex seems not to be an independent risk factor for early mortality in isolated CABG surgery. However, renal impairment, diabetes and obesity seem to play an important role in the operative risk profile of women undergoing isolated CABG.